An integrated approach of bioassay and molecular docking to study the dihydroxylation mechanism of pyrene by naphthalene dioxygenase in Rhodococcus sp. ustb-1. (June 2015) - Jin, Jing-Nan; Yao, Jun; Zhang, Qing-Ye; Yu, Chan; Chen, Peng; Liu, Wen-Juan; Peng, Dan-Ning; Choi, Martin M.F.
Highlights: The strain ustb-1 is firstly used in the biodegradation of pyrene. The results prove that C4–C5 positions on pyrene are suitable for dihydroxylation. A feasible dihydroxylation pathway of pyrene is proposed. Abstract: Naphthalene dioxygenase (NDO) is the initial enzyme catalyzing the biodegradation of aromatic compounds, and it plays a key role in microbial remediation of polluting sites. In this study, Rhodococcus sp. ustb-1 derived from crude oil was selected to investigate the biodegradation characters and dihydroxylation mechanism of pyrene by an integrated approach of bioassay and molecular docking. The biodegradation experiment proved that the strain ustb-1 shows high effective biodegradability to pyrene with a 70.8% degradation on the 28th day and the metabolite pyrene cis-4, 5-dihydrodiol was found. The results of molecular docking indicated that the regions surrounding pyrene are defined by hydrophobic amino acids which are favorable for the binding of dioxygen molecule at C4 and C5 positions of pyrene in a side-on mode. The binding positions of dioxygen are in agreement with the mass spectral analysis of the metabolite pyrene cis-4, 5-dihydrodiol. In summary, this study provides a promising explanation for the possible binding behavior between pyrene and active site of NDO.